2021
DOI: 10.1007/s40618-021-01561-0
|View full text |Cite
|
Sign up to set email alerts
|

Serum concentrations of dihydrotestosterone are associated with symptoms of hypogonadism in biochemically eugonadal men

Abstract: Purpose Symptoms of hypogonadism are often reported by subjects with normal serum testosterone (T) levels. We aimed to assess the association between clinical symptoms in andrological outpatients and sex steroids levels. Methods This is a retrospective cross-sectional cohort study in an Academic clinic and research unit. International Index of Erectile Function (IIEF, EF domain) and Aging Males Symptoms scale (AMS) questionnaires were completed by 635 and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 69 publications
0
2
0
Order By: Relevance
“…on hypogonadism patients, sexual functions were evaluated using IIEF and Aging Male’s Symptoms (AMS) questionnaire, and the relationship between the results and dihydrotestosterone was investigated. According to the study results, the dihydrotestosterone level was associated with hypogonadism symptoms in hypogonadism patients ( 24 ). A study conducted by Rosen and cols., which aimed to show the effect of TRT on the quality of life and sexual functions, reported that TRT increases the quality of life and improves the sexual functions of patients.…”
Section: Discussionmentioning
confidence: 94%
“…on hypogonadism patients, sexual functions were evaluated using IIEF and Aging Male’s Symptoms (AMS) questionnaire, and the relationship between the results and dihydrotestosterone was investigated. According to the study results, the dihydrotestosterone level was associated with hypogonadism symptoms in hypogonadism patients ( 24 ). A study conducted by Rosen and cols., which aimed to show the effect of TRT on the quality of life and sexual functions, reported that TRT increases the quality of life and improves the sexual functions of patients.…”
Section: Discussionmentioning
confidence: 94%
“…144 Some websites only provide high dosages of PDE5i, without mentioning the suggested "starting" dose for any naïve patient. 57 Additionally, first-line treatments for ED include pursuing a healthier lifestyle, such as by limiting alcohol intake, reducing harm from tobacco smoking and performing physical exercise 112,145,146 : individuals buying "sexual enhancers" online, or getting them from friends without any prior clinical evaluation, are generally less aware of the pathophysiology of sexual dysfunctions 115 and thus less likely to investigate for any underlying condition, such as endocrine dysfunctions including hypogonadism 147,148 and diabetes, 138,149,150 or metabolic and cardiovascular diseases, 150 −152 possibly resulting in ED. 136,153 The unsupervised use of PDE5i might therefore reduce the rate of diagnosis for ED-associated diseases.…”
Section: Health Risks Of Unsupervised Use Of Counterfeit Pde5imentioning
confidence: 99%